Fram strait—possible key to saving arctic ice - Ivanova, Detelina; Bhattacharyya, Subarna; Mlaker, Velimir; Strawa, Anthony; Field, Leslie; Player, Tim; Sholtz, Alexander (Frontiers in Climate, 2025)
Arctic amplification caused by global warming is accelerating an unprecedented loss of Arctic sea ice due to thinning of multi-year sea ice and increased export through Fram Strait, which is the largest Arctic gateway for ice export. The transition to a thinner and younger Arctic ice cover has resulted in a steady surface albedo decline of 1.25–1.51% per decade, weakening the radiative cooling effect of sea ice by 0.04–0.05 W m–² per decade. The Fram Strait ice export (FSIE) is a major sink in the Arctic ice mass balance, accounting for approximately 14% of the annual sea ice volume loss. As the ice becomes thinner, it drifts faster, leading to enhanced ice export. The annual and summer FSIE have increased by about 6% and 11% per decade, respectively, further accelerating Arctic sea ice decline. Surface Albedo Modification (SAM) has been considered among variety of climate intervention solutions to slow down the transition of the Arctic into a seasonally ice-free ocean by mid-century, in concert with the greenhouse emissions mitigation efforts. Using climate model simulations, we evaluate the impacts of SAM application on the Arctic radiation budget and ice cover in two deployment scenarios: Arctic-wide and regional in Fram Strait. We model such an increase in sea ice albedo as a perturbation to the present-day climate state. Our results show that enhancing the surface albedo by up to 20% Arctic-wide during summer reduces the absorbed radiation at the surface by 11.16 W/m² and increases outgoing radiation at the top of the atmosphere by 10.70 W/m². This results in surface cooling of –1.33°C and recovers approximately 10% of the present-day Arctic sea ice radiative cooling power. These findings suggest that large-scale surface albedo modification could offset Arctic warming and contribute measurably to global cooling. The regional targeted deployment in Fram Strait yields more spatially limited but dynamically significant responses. SAM in Fram Strait enhances surface albedo both locally and in adjacent regions (Barents, Kara Sea) through advection of thicker, more reflective ice. The resulting radiative cooling alters atmospheric circulation, strengthening the low-pressure system over the Barents–Kara sector and triggering a negative Arctic Dipole pattern. This reduces sea-ice export by 2.4% through Fram Strait via weakening the Transpolar Drift in addition to the local thickening and slowing of the ice in the FS region, supporting ice retention within the Arctic basin. Furthermore, the modified atmospheric circulation induces dynamically driven nonlocal ice growth in areas of Central Arctic which persist year-round. These results highlight the potential of Fram Strait albedo enhancement to support multi-year ice recovery and reduce its loss via the Fram Strait. While basin-wide SAM offers the greatest potential benefits, it remains logistically challenging and carries higher risks of unintended consequences. Targeted regional interventions—such as in the Fram Strait and marginal seas (Barents, Kara, and Beaufort)—present a more feasible and cost-effective alternative, with lower risks and the potential to induce basin-wide responses through coupled atmosphere–ice–ocean interactions. These regions are dynamically linked to major circulation centers, including the Barents–Kara Low and Beaufort High, making them promising leverage points for intervention. A strategy for Arctic climate intervention, where a coordinated, regionally targeted, and seasonally adaptive deployment—combining summer albedo enhancement with winter ice thickening—may offer the greatest potential to stabilize Arctic sea ice while minimizing risks.